ANALISIS DETERMINAN DIGITAL FINANCIAL LITERACY : PERBANDINGAN GENERASI Z DAN Y - Kezia Pearly Sembel; Sita Deliyana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
: The development of the world and technology in this era have begun to accelerate and become more complex. The presence of digital financial services makes life simpler for individuals, as even financial institutions are gradually adapting to the digitalization process. In 2007, the number of users of financial technology reached 7%; in 2011, it increased by 20%; in 2014, it increased by 36%; and by 2017, it reached 78%. Consequently, there is no doubt that this has become a requirement for human beings, particularly generations Z and Y, when conducting purchasing and selling transactions, transfers, etc. This condition is certainly intriguing to discuss, as there are differences between generation Z and generation Y in their use of financial technology facilities and services; therefore, the purpose of this study is to examine the generational differences that have an impact on Digital Financial Literacy. This study aimed to identify generational disparities in digital financial literacy based on age, gender, income, and marital status. This quantitative study employed a certain type of data collection using an online questionnaire through a Google form. There is a total of 226 respondent samples that can be analysed. In this research, exploratory factor analysis (EFA) was used to analysed the data. With the results of the research, it is necessary to increase learning about digital financial literacy, as well as to differentiate practical litis for employees, entrepreneurs, and students. Furthermore, it is necessary to optimize the factors that are highly significant and have a positive coefficient in digital financial literacy, including education level, income, occupation, and gender. In order to enhance digital financial literacy, socioeconomic and demographic factors must also be taken into account.